Acute and long-term procedural outcomes, arrhythmia recurrence and mortality after supraventricular arrhythmia ablation: a comparative study of fluoroscopy and zero-fluoroscopy guided techniques - Kamilla Luca Dávid; Kamilla Luca Dávid; Balázs Polgár; Péter Bógyi; Zsolt Bári; István Marczell; Manuella Bogdan; Zalán Gulyás; Mirjam Franciska Turáni; Judit Papp; Előd János Zsigmond; Emese Tóth-Zsámboki; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsZero-fluoroscopy (ZF) catheter ablation eliminates radiation exposure via use of 3-dimensional electroanatomical mapping. We aimed to assess safety and efficacy of ZF catheter ablation in the treatment of supraventricular tachycardias (SVTs), examine learning-curve characteristics and to evaluate long-term results and mortality.MethodsWe analysed clinical characteristics, procedural and follow-up data of 605 consecutive patients undergoing catheter ablation for SVT (atrioventricular nodal re-entry tachycardia, n = 297; atrial flutter, n = 241 and accessory pathway mediated tachycardia, n = 67) between June 2017 and September 2021. Procedures were either guided by conventional fluoroscopy (F, n = 223) or by EnSite Precision mapping system (ZF, n = 382) based on decision of the operating physician.ResultsAcute procedural success rate exceeded 98% across all arrhythmia groups for both ZF and F techniques (ZF: 99%, F: 100%, p = NS). 63% of patients underwent ZF procedures. Complication rate was low (0.66%), occurring only in the F group. Conversion rate to fluoroscopy was 7.8%. ZF procedures took an average of 5.1 min longer (ZF: 64.5 ± 24.3 min vs. F: 59.4 ± 29 min, p < 0.05), however ZF procedure times were reduced over time. At 3.2 years, total mortality was 7% with no significant difference between ZF and F. Deaths were not related to the procedures. Atrial flutter showed significantly higher recurrence in ZF compared to F (83% vs. 94%, p < 0.005).ConclusionCatheter ablation of SVTs using zero-fluoroscopy approach have similar acute success, complication and mortality rate as conventional fluoroscopic interventions. However, we detected significantly higher long-term arrhythmia recurrence after ZF ablation of atrial flutter, meriting further investigation.